Function of plasma membrane microdomain-associated proteins during legume nodulation. (3rd October 2017) - Qiao, Zhenzhen; Libault, Marc
ABSTRACT: Plasma membrane microdomains are plasma membrane sub-compartments enriched in sphingolipids and sterols, and composed by a specific set of proteins. They are involved in recognizing signal molecules, transducing these signals, and controlling endocytosis and exocytosis processes. In a recent study, applying biochemical and microscopic methods, we characterized the soybean GmFWL1 protein, a major regulator of soybean nodulation, as a new membrane microdomain-associated protein. Interestingly, upon rhizobia inoculation of the soybean root system, GmFWL1 and one of its interacting partners, GmFLOT2/4, both translocate to the root hair cell tip, the primary site of interaction and infection between soybean and Rhizobium . The role of GmFWL1 as a plasma membrane microdomain-associated protein is also supported by immunoprecipitation assays performed on soybean nodules, which revealed 178 GmFWL1 protein partners including a large number of microdomain-associated proteins such as GmFLOT2/4. In this addendum, we provide additional information about the identity of the soybean proteins repetitively identified as GmFWL1 protein partners. Their function is discussed especially in regard to plant-microbe interactions and microbial symbiosis. This addendum will provide new insights in the role of plasma membrane microdomains in regulating legume nodulation.